1-Phenyl-N-(benzothiazol-2-yl)methanimine derivatives as Middle East respiratory syndrome coronavirus inhibitors. Issue 71 (7th December 2020) - Hu, Min-Qi; Li, Heng; Lin, Ying; Zhang, Ying; Tang, Jie; Zuo, Jian-Ping; Yu, Li-Fang; Tong, Xian-Kun; Tang, Wei; Yang, Fan
Abstract : A series of novel 1-phenyl- N -(benzothiazol-2-yl)methanimine derivatives were synthesized and their in vitro inhibitory potencies were evaluated on MERS-S pseudovirus. Abstract : Middle East respiratory syndrome coronavirus (MERS-CoV) poses a serious threat to human health, and currently there are no effective or specific therapies available to treat it. Herein a series of 1-phenyl- N -(benzothiazol-2-yl)methanimine derivatives with inhibitory activity against MERS-CoV are described. The compound 4f with a 50% inhibition concentration value of 0.09 μM is a promising inhibitor that warrants further evaluation, towards the development of potential anti-MERS-CoV drugs.